Therapeutic Communication in Schizophrenic Patients: A Systematic Literature Review - Nompo, Rifki Sakinah (HM Publisher, 2023)
Introduction: Schizophrenia is a complex mental disorder that affects an individual's thoughts, perceptions, and behaviors. Therapeutic communication in schizophrenic patients refers to the communication approach used by health professionals or therapists to interact with schizophrenic patients with the aim of assisting them in recovery and improving their quality of life. This study aimed to explore forms of therapeutic communication that could be used to improve improvements in schizophrenia patients. Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding therapeutic communication and schizophrenia. The search was performed using the terms